Power and the Conquest of Moral-Legal Values - Trajković, Marko; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Abstract: The power of values ​​and law can go together, the only question remains where this common path will take them. It seems that in society, power is best distributed as a desire, because most everyone wants it. When that power as an experience is connected to the highest instances of power, the matter takes on very serious dimensions. Then power also has formal-legal force expressed in legal regulations with imperative force, especially in the domain of criminal law. Power in its unlimited form stands in opposition to freedom, that is, my freedom is the limit to your power. Then a conflict arises, because no one wants to limit their power. But limitation is necessary because otherwise this leads to pure voluntarism. Any order that pleads for the durability of its foundation must be based on permanent foundations, which are power and sanctions. These foundations must be found in the world of values, which will then be lowered into reality, which in this case can be designated as a social community and the state. Thus, it is possible for values, instead of power, to become an integral part of legal regulations.